2010
DOI: 10.1063/1.3430633
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies of the effects of precursor plasma on the performance of wire-array Z-pinches

Abstract: This paper is to numerically investigate, in one dimension, the effects of precursor plasma resulted from wire-array ablation on the performance of its following implosion after the ablation. The wire-array ablation is described by an analytic model, which consists of a rocket model or Sasorov's expression of wire-array mass ablation rate, the evolution equation of magnetic field, and several roughly reasonable assumptions. The following implosion is governed by the radiation magnetohydrodynamics. The implosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…From our simulation results, the dependence of the maximum radial velocity V a on the ratio of interwire gap/core size D g /d can be approximately expressed by the formula V a = 1.61×10 7 (1−0.8e (−Dg/3.8d) ), which is similar to that obtained from the experimental observations on MAGPIE [44]. Previous studies have shown that the existence of the precursor column resulted in higher x-ray power [45]. If the interwire separation is too small, the radial velocity of ablated plasmas would be very low and the precursor column would not be formed before the implosion phase and that might lead to decrease in x-ray power.…”
Section: Ablation and Initializationsupporting
confidence: 83%
“…From our simulation results, the dependence of the maximum radial velocity V a on the ratio of interwire gap/core size D g /d can be approximately expressed by the formula V a = 1.61×10 7 (1−0.8e (−Dg/3.8d) ), which is similar to that obtained from the experimental observations on MAGPIE [44]. Previous studies have shown that the existence of the precursor column resulted in higher x-ray power [45]. If the interwire separation is too small, the radial velocity of ablated plasmas would be very low and the precursor column would not be formed before the implosion phase and that might lead to decrease in x-ray power.…”
Section: Ablation and Initializationsupporting
confidence: 83%
“…17 Previous studies have shown that the existence of the precursor column resulted in higher x-ray power. 27 If the interwire separation is too small, the radial velocity of ablated plasmas would be very low and the precursor column would not be formed before the implosion phase and that might lead to decrease in x-ray power. The calculational results can be used to explain the experimental observation that the x-ray power decreases once a critical wire number is exceeded.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the practice of Z-pinch simulation, which is mostly based on the radiation magnetohydrodynamics equations (model), for obtaining better simulation results, which agree well with the experimental data, such as convergence ratio, and x-ray power and energy, the electrical resistivity of Zpinch plasma needs artificially modifing more or less. [12,14] The characteristic results might be obtained through this modification, but the magnetic field evolution and the pinch dynamic process might be changed unexpectedly. It is interesting and important to explore the variations of the magnetic field evolution and the dynamic process with this modification.…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of measured images from the wire-array (without preconditioning) Z-pinch experiments to demonstrate that the majority of wire-array substance has been ablated due to Joule heating and is radially swept inward towards the array axis by 𝑗 × 𝐵 force, while the wire-cores keep stationary at their original positions before its implosion begins. [7][8][9][10][11][12] So actually inside the wire-array is prefilled with ablated plasma, whose density varies with time and radius. It is possibly very low sometime and somewhere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation